Meterological and stable carbon, oxygen and clumped isotope data of land snails from Europe - Gábor Újvári; László Rinyu; Anna Sulikowska-Drozd; Barna Páll-Gergely; Stefano M Bernasconi (PANGAEA, 2024)
These data include site information and collection dates of land snails (Clausilia pumila, Succinella oblonga, Trochulus hispidus), meteorological data of collection sites using the ClimateEU software, as well as carbon, oxygen and clumped isotope compositions of snail shells of the mentioned three species from culturing experiments and natural populations across Europe. During the laboratory experiments at the University of Lodz (Poland) individuals of the three species were kept at 12, 18 and 24 °C temperatures in climate chambers, fed exclusively by fresh lettuce and humidity was controlled using tap water (δ^1?O: -9.29 ±0.52 extperthousand, V-SMOW). δ^1^3C, δ^1?O and Δ?? values of snail shells from lab experiments and field-collections were determined in two laboratories (Institute for Nuclear Research, Debrecen, and Geological Institute, ETH Zürich) using IRMS. Detailed analysis and interpretations of the results obtained can be read in the original publication.